The Nexus Between Irans Feminism and Islamic Revolution in Persepolis: A Feminist Critique (Philosophy and Progress, 2017)
Persepolis (2007) is the distressing story of a young girl in Iran during the Islamic Revolution. It is through the eyes of the bright and candid 9-year-old Marjane that we see popular optimisms darted as fundamentalists take power and forcing the veil on women and imprisoning thousands. Intelligent and intrepid, Marjane outwits the "social guardians" and ascertains punk, ABBA, and Iron Maiden. Hitherto when her uncle is inanely put to death and as bombs fall around Tehran in the Iran/Iraq war, the everyday panic that saturated existence in Iran is obvious. Persepolis, an animated film by Marjane Satrapi and Vincent Paronnaud, is based on the four volumes of Satrapis extensively read autobiographical detail narrative of the identical name. It informs the account of contemporary Iran through the life of a girl with impressive aspirations: to be the galaxys last prophet and to shave her legs. Contradictory concepts in one existence throughout the film knit together the turbulent history of Iran and Marjanes turbulent life. She was nine years old when the waves of revolution had risen to engulf the country. Waves that send her parents to the demonstrations, bring politics into her childhood games, free prisoners from the dungeons of the Shah Pahlavi regime, and finally lead to the overthrow of the monarchy. In the first part of the film, through a look at the life and struggle of three generations of Marjanes family, we are introduced to a history of dictatorship, oil and dependency, rebellion and revolution, suppression and more rebellion. Throughout the representation of the movie, the present study examines the dilemmas that women were facing with different political shifts as well as how the opportunist male politicians use and abuse women in order to maintain their patriarchal supremacy.Philosophy and Progress, Vol#57-58; No#1-2; Jan-Dec 2015